Implementasi Keterampilan Dasar Master Of Ceremony (MC) - Hamama, Syifa; Kusumaningratri, Rose; Zulfiyani, Afrida (IAINU Kebumen, 2022)
The ability of an MC (Master Of Ceremony) in hosting an event will determine the success of organizing an event. An MC is not only required to have good public speaking skills but also to be smart, assertive, able to make decisions and look good. An MC must have the ability to build a solemn, respectful and official atmosphere in formal events. The MC's job is to ensure that the event runs smoothly, on time, lively, memorable, and according to the schedule or event rundown. For this reason, basic skills that must be owned and learned by an MC are needed including vocal, verbal and visual.